Recycling of eggshell waste into low-cost adsorbent for Ni removal from wastewater. (15th October 2017) - De Angelis, Gabriele; Medeghini, Laura; Conte, Aida Maria; Mignardi, Silvano
Abstract: The disposal of about 8 million ton/year of eggshell waste produced worldwide is an environmentally challenging issue. However, this waste can be converted to new materials useful for several industrial applications. In this study, hydroxyapatite was synthesized from eggshell waste and used as adsorbent for Ni 2+ removal from aqueous solutions. Eggshell-derived hydroxyapatite was characterized using X-ray diffraction, scanning electron microscopy with the energy dispersion spectrum analysis and Fourier transform infrared spectroscopy. Batch experiments were conducted to investigate the effects of contact time and initial Ni 2+ concentration on the adsorption process. Adsorption equilibrium was achieved within 80 min. The kinetics of the adsorption process was studied applying pseudo-first-order, pseudo-second-order and intraparticle diffusion kinetics models. The kinetics study showed that the pseudo-second-order kinetic model described well the adsorption process with high correlation coefficient. The maximum Ni 2+ adsorption capacity was found to be 109 mg g −1 which is generally higher than other waste-derived adsorbents. The adsorption of Ni 2+ on eggshell-derived hydroxyapatite was well fitted by the Langmuir equation as compared to Freundlich, Temkin and Dubinin-Radushkevic isotherm models. The removal mechanism of Ni 2+ by eggshell-derived hydroxyapatite could involve ion exchange with Ca 2+ and dissolution/precipitation of the starting hydroxyapatite resulting in the formation of a Ni-bearing phosphate. The results of the present study showed that hydroxyapatite synthesized from eggshell waste represents an excellent low-cost adsorbent for treatment of Ni 2+ contaminated waters. Graphical abstract: Highlights: Facile synthesis of hydroxyapatite using eggshell waste. The adsorbent potential in removing Ni 2+ from aqueous solutions was evaluated. 91% Ni 2+ removal was achieved within 80 min. Ni 2+ removal involves ion exchange and precipitation of Ni-bearing phosphate. The use of eggshell-waste based adsorbent contributes to waste minimization.